Comparative Characterization of Modern Methods for the Indication of the Human Immunodeficiency Virus (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Human immunodeficiency virus virus (HIV) world along the most big social and economic from problems one HIV - infected people number year gradually increasingly is going on, this and international health storage to the system big pressure (UNAIDS, 2022). Since the 1980s, HIV and his/her complications AIDS (Human Immunodeficiency Virus) shortage syndrome ) world on a scale many of people his life danger under put it. The virus early to be determined and control under to be taken of the disease spread prevent to take and of patients life quality in improvement important role plays (Smith and Johnson, 2020).